The effect of selenium and tocotrienol supplementation on the muscle contractile properties, fatigue, EMG and antioxidant status of gastrocnemius muscle of trained and untrained rats - Alwan, Mohand R. (2009)
Exercise induces radical-mediated oxidative damage of skeletal muscle membranes which has been implicated in the fatigue process. Selenium (S) is an important component of cellular selenocompounds and is an integral component of glutathione Peroxidase (GPx), which catalyze the reduction of harmful peroxides. Tocotrienol (T) is a major chain breaking antioxidant that has been shown to reduce contraction mediated oxidative damage. We hypothesized that Sand T supplementation would positively affect muscle contractile function and increase antioxidant enzymes activities during exercise. To test this postulate, were used sixty-four male Wistar-Kyoto rats at weight between 300-350g randomized into eight groups with eight rats per group rats these sample size was calculated using PS software based on comparing two means of superoxide dismutase (SOD). The rats were fed with either S (80 μg/kg body weight) or T (8 mg/kg body weight) and also with combination of S and T diet in sedentary and jumping exercise which consisted from 40 jumps for 40 cm in height for 5 days per week for 6 weeks. Upon completion of the feeding period, animals were anesthetized with an intraperitoneal injection of sodium pentobarbital ( 40 mg/kg); the sciatic nerve was located and cut and tendon of the TA muscle was cut close to the bone and attached to an isometric force transducer (AD Instrument, model 400) with computer-based data acquisition system (AD Instrument, Power Lab® and Chart software. The muscle contractile properties were measured, fatigue protocol consisted of trains of pulses composed of fourteen pulses recurring at 40 Hz repeated every 1 s for at least 2 min in order to assess sensitivity to fatigue. There were significant (P<0.05) differences in the muscle contractile properties (Pt, Po, Pt/Po Ratio and CT), also decrease in EMG failure and increase of fatigue index between S, T and control animals and this difference was still greater in combined supplementation of S and T group of exercised rats. The stimulated MG muscle from the exercised S and T supplemented animals had significantly (P<0.05) higher antioxidant enzymes activity in both GPx, CAT and decreased lipid hydroperoxidation as compared to the same muscles in control animals as well as in comparison with sedentary supplementation. Most effective results were observed in combined S and T supplementation animals in exercise group as compared with sedentary supplementation groups. This data support the hypothesis that S and T supplementation in exercised animals increases muscular endurance and improves muscle contractile properties following a prolonged series of contractions.